Inhaled tyrosine kinase inhibitors for pulmonary hypertension: a possible future treatment - Pitsiou, Georgia (Dove Medical Press, 2014)
Pulmonary hypertension is a disease with severe consequences for the human body. There are several diseases and situations that induce pulmonary hypertension and are usually underdiagnosed. Treatments include conventional medical therapies and oral, inhaled, intravenous, and subcutaneous options. Depending on its severity, heart or lung transplant may also be an option. A possible novel treatment could be tyrosine kinase inhibitors. We conducted experiments with three jet nebulizers and three ultrasound nebulizers with erlotinib, gefitinib, and imatinib. Different residual cup designs and residual cup loadings were used in order to identify the best combination to produce droplets of less than 5 μm in mass median aerodynamic diameter. We found that gefitinib could not be transformed into a powder, so conversion to an aerosol form was not possible. Our experiments indicated that imatinib is superior to erlotinib with regard to small droplet size formation using both inhaled technologies (1.37 μm <2.23 μm and 1.92 μm <3.11 μm, jet and ultrasound, respectively) and, at jet devices (1.37 μm <1.92 μm). Cup designs C and G contribute best to small droplet creation uniquely supporting and equally well the activity of both drugs. The disadvantage of the large droplets formed for erlotinib was offset when combined with residual cup C (1.37 μm instead of 2.23 μm). At a 2 mL dose, the facemask and cone mouthpieces performed best and evenly; the facemask and low dose were the best choice (2.08 μm and 2.12 μm, respectively). Erlotinib and imatinib can be administered as an aerosols, and further in vivo experimentation is necessary to investigate the positive effects of these drugs in the treatment of pulmonary hypertension.